The medieval French Alexander - Maddox, Donald; Sturm-Maddox, Sara (SUNY series in medieval studies., 2002)
"Alexander the Great was one of the legendary Nine Worthies in the medieval canon of ancient and modern heroes, and medieval writers exploited his legend in a wide variety of literary and didactic texts. Addressing the classical legacy to the Middle Ages as expressed in four centuries of vernacular narratives, this volume offers the first systematic collective study of Alexander the Great's thematic prominence in medieval culture. Contributors from Britain, France, the Netherlands, and the United States combine sensitive textual analyses with perspectives from such diverse fields as art history, codicology, anthropology, sociology, the history of mentalities, and postcolonial theory. Overall, the collection offers a provocative rethinking of the monumental medieval French tradition of Alexander the Great, as well as valuable insight into the emergence and transformations of French literature between the early twelfth century and the end of the Middle Ages."--Jacket